2014
DOI: 10.1002/pi.4711
|View full text |Cite
|
Sign up to set email alerts
|

Atom transfer radical polymerization of an epoxide‐containing monomer, 4‐vinylphenyloxirane, employing low concentration of catalyst: synthesis of linear and star‐shaped macromolecules

Abstract: 4-Vinylphenyloxirane (4VPO) was homopolymerized under initiators for continuous activator regeneration atom transfer radical polymerization (ATRP) conditions using diethyl 2-bromo-2-methylmalonate, ethyl 2-bromoisobutyrate, as well as tri-, tetraand hexafunctional 2-bromisobutyrates as the initiators to yield well-defined linear and star-shaped epoxide-containinghomopolymers. In addition, the chain extension of Br-capped polystyrene with 4VPO afforded well-defined block copolymers. All polymerizations employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…4‐Vinylphenyloxirane (4VPO) was synthesized as previously reported, with the exception that the solvent used in the first step was changed to CS 2 . The RAFT chain transfer agents (CTAs) butyl 1‐phenylethyl trithiocarbonate (BPT), 2‐cyano‐2‐propyl dodecyl trithiocarbonate (CDT), benzyl dithiobenzoate (BDB), and 2‐(butylsulfanylthiocarbonylsulfanyl)‐2‐methyl propionic acid (BMPA) were synthesized according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…4‐Vinylphenyloxirane (4VPO) was synthesized as previously reported, with the exception that the solvent used in the first step was changed to CS 2 . The RAFT chain transfer agents (CTAs) butyl 1‐phenylethyl trithiocarbonate (BPT), 2‐cyano‐2‐propyl dodecyl trithiocarbonate (CDT), benzyl dithiobenzoate (BDB), and 2‐(butylsulfanylthiocarbonylsulfanyl)‐2‐methyl propionic acid (BMPA) were synthesized according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Epoxides are often utilized as synthetic intermediates in the production of aziridines. A renewed interest in epoxide‐containing styrenic monomers and their applications in macromolecular design has recently resulted in several new high‐yielding methods for their production . One such monomer, 4‐vinylphenyloxirane (4VPO), proved to be especially convenient as a starting material for the synthesis of styrenic monomers containing activated aziridines (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that epoxides can act as reducing agents in low-catalyst concentration ATRP reactions (Scheme 2) (50,57), and in the chain extension reactions reported here, the epoxides present in the macroinitiator served to regenerate the lower oxidation state metal complex (activator) via reduction of the higher oxidation state deactivator.…”
Section: Chain Extension Of Hb-polygma-br X Via Low-catalyst Concentrmentioning
confidence: 95%